Wyboje na „drodze do Europy”. Nowa odsłona kina drogi i ponowne mapowanie narodu w Europie Środkowej po 2004 roku - Michael Gott; Kris Van Heuckelom (Annales Universitatis Paedagogicae Cracoviensis. Studia de Cultura, 2020)
This paper is dedicated to the analysis of the development of Central European road movies after 2004, with special consideration given to Polish and Czech cinematography. The films which have been discussed are Polish productions Francuski numer (2006, directed by Robert Wichrowski) and Handlarz cudów (2009, directed by Bolesław Pawica and Jarosław Szoda), as well as Czech Rodina je základ státu (2011, directed by Robert Sedláček) and Pusinky (2007, directed by Karin Babinská). Although these films – to a certain extent – follow the fixed paths, we put forward the assumption that at the same time, they use the tools of road movies in an innovative and varied manner, responding to problems, dilemmas and perspectives of Central Europe after 2004.